2018
DOI: 10.47672/jsm.338
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change Managementand Employee Performance in Public Sector Organizations in Kenya: Case of the Parliamentary Service Commission

Abstract: Purpose: The purpose of this study was to analyze the effect of structural change management on employee performance in the Parliamentary Service Commission (PARLSCOM) and it was undertaken through descriptive research design. Methodology: The study targeted all the nine hundred and fourteen employees of PARLSCOM. Stratified and simple random sampling techniques were used to select a sample of ninety one participants from the target population.  Self-administered questionnaire and interview guides were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Odero et al (2019) while studying the impact ofistrategicileadershipioniperformanceioficommercial iand financial state corporationsiiniKenya, discovered that, a balanced organizational control in the management of human, financial, and social capita plus the organizational culture was effective towards the realization of good performance. Odero et al, (2019) This was also the outcome in a case study by Jumanne and Njoroge (2018) Further, Rigii, Ogutu, Awino, and Kitiabi (2019) emphasized that county leadership has to incorporate strategic leadership and innovatively train its employees for improved service delivery. Their scope was limited as it did not include resource allocation or execution of policy regulations in the devolved units.…”
Section: Strategic Leadership Practicesmentioning
confidence: 81%
“…Odero et al (2019) while studying the impact ofistrategicileadershipioniperformanceioficommercial iand financial state corporationsiiniKenya, discovered that, a balanced organizational control in the management of human, financial, and social capita plus the organizational culture was effective towards the realization of good performance. Odero et al, (2019) This was also the outcome in a case study by Jumanne and Njoroge (2018) Further, Rigii, Ogutu, Awino, and Kitiabi (2019) emphasized that county leadership has to incorporate strategic leadership and innovatively train its employees for improved service delivery. Their scope was limited as it did not include resource allocation or execution of policy regulations in the devolved units.…”
Section: Strategic Leadership Practicesmentioning
confidence: 81%
“…Therefore, organisations should keep an eye on their current structure to see whether or not it matches the goals they have set for themselves and modify/adjust it if necessary. Similarly, Jumanne and Njoroge (2018) argue that to improve the effectiveness of employee performance in public organisations, the roles and responsibilities of each employee should be clearly defined and consider merging similar roles and departments to avoid confusion. This is because improved management systems, work structures and administrative procedures facilitate successful business growth.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…realized that the burden of accountability squarely lies on the counties although decision making and resource management authority still remains with the national government. Ochieng (2017); Jumanne & Njoroge (2018) suggested that this relation requires the right accountability and coordination mechanism. This study investigated communication and access to information, social audits and publication of citizens' budgets as measures for leadership accountability.…”
Section: Public Accountability Practices and Devolved Administrative ...mentioning
confidence: 99%